Comprehensive Examination on Intentions of Students in Social Entrepreneurship - MONIR Maruf Mohammad Sirajum; GEBEREMESKEL Aula Nerea (Applied Research in Administrative Sciences)
The capacity to affect change on a local and global scale about a range of political, social, environmental, and economic challenges is known as social entrepreneurship (SE). Young exposure to theory and practice of social entrepreneurship at postsecondary educational institutions is thought to influence this change. In this study, we examine the intentions of students in social entrepreneurship. This study's objective is to assess the degrees of social and entrepreneurial entrepreneurship. For the study, 150 college students served as the sample. This study examines empathy, moral duty, social support, self-efficacy, social impact, and educational level as principal motivators for social entrepreneurship intentions. The SPSS is a software program used to analyse the data and perform statistical analyses. The findings indicate that the only factors that were statistically correlated with the desire to engage in social entrepreneurship were empathy, self-efficacy, and psychological support. The association between social support and the ambitions for social entrepreneurship was shown to be unfavourable. In conclusion, the study provides insightful information for practitioners and educators who aim to foster a vibrant environment for student social entrepreneurship.